Surface material of sanitary material and method for producing the same

By adopting a laminated structure of cotton fiber web with long fibers and extremely fine fiber nonwoven fabrics in the sanitary material surface material, and using high-pressure water flow to entangle the fibers, the problem of both wear resistance and skin touch in the prior art is solved, and a surface material with high wear resistance and good touch is achieved.

CN115917070BActive Publication Date: 2025-04-22ZUIKO CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180045538.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-02
Filing Date
2021-06-23
Publication Date
2025-04-22
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

The surface materials of existing sanitary materials are difficult to maintain a good skin touch when improving wear resistance.

Method used

The cotton fiber web composed of cotton fibers is used to form a cotton fiber, a long fiber non-woven fabric containing a propylene polymer and an extremely fine fiber non-woven fabric laminate, and the extremely fine fiber non-woven fabric is entangled with the cotton fiber by high-pressure water flow treatment, thereby improving the wear resistance of the surface material.

Benefits of technology

It is achieved that the wear resistance of the sanitary material surface material is significantly improved without reducing the skin touch, and the wear resistance of the skin contact surface is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115917070B_ABST
    Figure CN115917070B_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a surface material of a sanitary material that improves wear resistance without reducing the skin touch of the surface in contact with the skin. The manufacturing method of the surface material of the sanitary material consists of the following steps. A cotton fiber web composed of cotton fibers is stacked with an SMS nonwoven fabric to obtain a laminate. Here, the SMS nonwoven fabric is formed by stacking a first long fiber nonwoven fabric, an ultrafine fiber nonwoven fabric, and a second long fiber nonwoven fabric in sequence. A high-pressure water flow is applied to the laminate to interweave the cotton fibers with each other and the long fibers with each other. In addition, the ultrafine fiber nonwoven fabric is destroyed by a high-pressure water flow, so that a large amount of ultrafine fibers flow out, and a part of the ultrafine fibers are retained and entangled in the interweaving part between the cotton fibers. Thereby, a surface material in which the bonding between the cotton fibers becomes firm is obtained. In the obtained surface material, the surface on the cotton fiber web side becomes the surface in contact with the skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a surface material used in a skin-contacting portion of sanitary materials such as sanitary napkins and disposable diapers, and in particular to a method for producing a surface material of a sanitary material having a good touch to the skin and excellent abrasion resistance. Background Art

[0002] In the past, short-fiber nonwoven fabrics or long-fiber nonwoven fabrics have been used as surface materials for sanitary materials. Although short-fiber nonwoven fabrics are excellent in skin touch, they have the disadvantage of low breaking strength. On the other hand, although long-fiber nonwoven fabrics have high breaking strength, they have the disadvantage of poor skin touch. Therefore, Patent Document 1 discloses a surface material for sanitary materials formed by joining long-fiber nonwoven fabrics with specific short-fiber nonwoven fabrics. Moreover, a material in which hot-melt composite short fibers of at least two thermoplastic resin components having a high melting point and a low melting point are fused to each other using the low-melting point component is used as the specific short-fiber nonwoven fabric arranged on the skin side (Patent Document 1, Claim 1). In addition, a material in which hot-melt composite long fibers of at least two thermoplastic resin components having a high melting point and a low melting point are fused to each other using the low-melting point component is also used as the long-fiber nonwoven fabric (Patent Document 1, Claim 3).

[0003] However, short fiber nonwoven fabrics composed of short fibers formed of thermoplastic resin components have poor skin touch compared to short fiber nonwoven fabrics composed of natural fibers such as cotton fibers and silk fibers, and may also cause skin rashes. Therefore, a surface material is proposed that uses a nonwoven fabric formed of cotton fibers as the short fiber nonwoven fabric and entangles and integrates long fibers in a long fiber nonwoven fabric with cotton fibers (Patent Document 2, Claim 1).

[0004] Patent Document 1: Japanese Patent Application Laid-Open No. 9-117470

[0005] Patent Document 2: Utility Model Registration No. 3218416 Summary of the invention

[0006] The present invention is an improved invention of the proposal described in Patent Document 2, and an object of the present invention is to improve the abrasion resistance without reducing the touch of the surface of the surface material that contacts the skin.

[0007] The present invention solves the above-mentioned problem by using a meltblown nonwoven fabric (e.g., Japanese Patent Publication No. 2019-209121), which is commonly used as a leakproof material for sanitary materials, as a raw material for the surface material and adopting a specific manufacturing method. That is, the present invention relates to a method for manufacturing a surface material of a sanitary material whose cotton fiber web side contacts the skin, characterized in that a high-pressure water flow is applied to a laminated body in which a cotton fiber web composed of cotton fibers, a first long fiber nonwoven fabric composed of long fibers containing propylene polymers, an ultrafine fiber nonwoven fabric containing ultrafine fibers, and a second long fiber nonwoven fabric composed of long fibers containing propylene polymers are sequentially stacked, thereby destroying the ultrafine fiber nonwoven fabric and entangled the cotton fibers with the ultrafine fibers, wherein the ultrafine fibers contain propylene polymers and have a fiber diameter thinner than the fiber diameters of the cotton fibers and the long fibers. In addition, it relates to a surface material of a sanitary material, including a cotton fiber web area composed of cotton fibers and an area containing long fibers containing a propylene polymer, wherein ultrafine fibers having a fiber diameter thinner than that of the cotton fibers and the long fibers are interwoven with the cotton fibers and the long fibers.

[0008] The method of the present invention is to apply a high-pressure water flow to a laminate containing an ultrafine fiber nonwoven fabric, destroy the ultrafine fiber nonwoven fabric, make a large amount of ultrafine fibers flow out, and make a part of the ultrafine fibers stay and entangle in the interlaced parts of the cotton fibers. Therefore, the cotton fibers of the surface material obtained by the method of the present invention become firmly bonded to each other, and the wear resistance of the cotton fiber mesh surface in contact with the skin is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a photograph of the surface of a laminate of first long fiber nonwoven fabric / ultrafine fiber nonwoven fabric / second long fiber nonwoven fabric (hereinafter, the laminate may also be referred to as "SMS nonwoven fabric") taken using an electron microscope at a magnification of 300 times. DETAILED DESCRIPTION

[0010] The cotton fiber web used in the present invention is mainly composed of cotton fibers. In addition to cotton fibers, hydrophilic fibers such as silk fibers or rayon fibers can be mixed. The cotton fiber web can be obtained by opening and aggregating cotton fibers using a known carding method. The weight per unit area of ​​the cotton fiber web is 10 to 20 g / m 2About. As cotton fiber, it is preferred to use undegreased cotton fiber (undegreased cotton), and it is further preferred to use undegreased and bleached cotton fiber (undegreased bleached cotton). Since undegreased cotton has residual oil components (cotton wax and cottonseed oil attached to the surface of raw cotton, etc.) on the surface of cotton fiber, body fluids are not easy to diffuse toward the surface direction of the surface material. Therefore, it is not easy to make the skin feel sticky when used, so it is preferred. In addition, undegreased bleached cotton is bleached into white, which gives a clean feeling to sanitary materials, so it is preferred. It should be noted that in this specification, the numerical range expressed by "~" refers to the range that includes the numerical values ​​recorded before and after "~" as the lower limit and upper limit.

[0011] The long fibers constituting the first long fiber nonwoven fabric and the second long fiber nonwoven fabric used in the present invention contain a polypropylene-based polymer. The surface material of the present invention has a tendency to have a better tensile strength because it includes regions from the first long fiber nonwoven fabric and the second long fiber nonwoven fabric. From the viewpoint of further improving the tensile strength of the surface material, the content of the long fibers in the long fiber nonwoven fabric is preferably 50% or more, more preferably 90% or more, and further preferably 99% or more based on the number of fibers. In addition, from the viewpoint of spinnability, the content of the propylene-based polymer in the long fibers is preferably 90% by mass or more, more preferably 99% by mass or more. It should be noted that in the numerical ranges recorded in stages in this specification, the upper limit value or lower limit value recorded in a certain numerical range can be replaced by the upper limit value or lower limit value of another numerical range recorded in stages. In addition, in the numerical ranges recorded in this specification, the upper limit value or lower limit value recorded in a certain numerical range can be replaced by the value shown in the examples.

[0012] As polypropylene polymers, propylene homopolymers, propylene α-olefin random copolymers or propylene α-olefin block copolymers can be used. Here, as α-olefins, ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene and other α-olefins other than propylene can be used. It should be noted that when α-olefins are copolymerized, the copolymerization amount is preferably 1 to 10 mol%. The fiber can contain one of these polymers alone or more than two. It should be noted that propylene polymers refer to polymers containing more than 50% by mass of structural units from propylene.

[0013] The melt flow rate (MFR, ASTM D1238, 230°C, load 2160g) of the propylene polymer contained in the long fiber is not particularly limited as long as it can be melt-spun. For example, the MFR can be 1g / 10min to 1000g / 10min, preferably 5g / 10min to 500g / 10min, and more preferably 10g / 10min to 100g / 10min. If the MFR of the propylene polymer is within the above range, there is a tendency for the tensile strength to increase, so it is preferred.

[0014] The average fiber diameter of the long fibers is not particularly limited as long as the effects of the present invention are exerted. From the viewpoint of further improving abrasion resistance and tensile strength, it is preferably 10 μm to 50 μm, and more preferably 11 μm to 30 μm. The average fiber diameter of the long fibers is a value calculated based on a photograph of the long fiber nonwoven fabric, as described later in the project of the embodiment. The photograph may be a photograph of the long fiber nonwoven fabric alone, a photograph of a laminate of an ultrafine fiber nonwoven fabric and a long fiber nonwoven fabric, or a photograph of the surface material. It should be noted that Figure 1 This is a photo taken of the surface of SMS nonwoven fabric.

[0015] The long fibers may be long fibers composed of a single component, or may be composite long fibers of a core-sheath type, an island-in-the-sea type, etc. From the viewpoint of further improving the strength of the surface material, long fibers composed of a single component are preferred.

[0016] The first long fiber nonwoven fabric and the second long fiber nonwoven fabric used in the present invention are generally produced by a so-called spunbond method. In addition, the first long fiber nonwoven fabric and the second long fiber nonwoven fabric are preferably partially heat-bonded by heat embossing to further improve the shape stability.

[0017] From the viewpoint of further improving the tensile strength and facilitating the entanglement treatment by the high-pressure water jet described later, the weight per unit area of ​​the first long-fiber nonwoven fabric and the second long-fiber nonwoven fabric is preferably 1 to 30 g / m 2 , more preferably 3 to 10 g / m 2 .

[0018] The ultrafine fiber nonwoven fabric sandwiched by the first long fiber nonwoven fabric and the second long fiber nonwoven fabric contains ultrafine fibers containing propylene polymers and having an average fiber diameter of 0.5 to 7 μm. The average fiber diameter of the ultrafine fibers is calculated based on a photograph taken of the ultrafine fiber nonwoven fabric as described later in the project of the embodiment. The photograph taken can be a photograph taken of the ultrafine fiber nonwoven fabric alone, a photograph taken of a laminate of the ultrafine fiber nonwoven fabric and the long fiber nonwoven fabric, or a photograph taken of the surface material. Moreover, a photograph with a fiber diameter of 8 μm or less is selected for calculation. Therefore, ultrafine fibers are fibers whose fiber diameter is 8 μm or less.

[0019] The monomers and amounts constituting the propylene polymer contained in the ultrafine fibers are the same as those of the propylene polymer contained in the long fibers. From the viewpoint of further improving abrasion resistance, the content of the ultrafine fibers in the ultrafine fiber nonwoven fabric is preferably 50% or more, more preferably 90% or more, and further preferably 99% or more based on the number of fibers. In addition, from the viewpoint of spinnability, the content of the propylene polymer in the ultrafine fibers is preferably 90% by mass or more, and more preferably 99% by mass or more.

[0020] The melt flow rate (MFR, ASTM D1238, 230°C, load 2160g) of the propylene polymer contained in the ultrafine fibers is not particularly limited as long as melt spinning can be performed. For example, the MFR can be 1g / 10min to 2000g / 10min, preferably 100g / 10min to 1500g / 10min, and more preferably 200g / 10min to 1000g / 10min. If the MFR of the propylene polymer is within the above range, there is a tendency for the strength of the ultrafine fibers to increase, so it is preferred. In addition, if the MFR of the propylene polymer is within the above range, it is easy to adjust the average fiber diameter to the specified range, and there is a tendency to more appropriately form the interweaving of fibers by water flow interweaving, so it is preferred. It should be noted that from the perspective of easier implementation of the interweaving treatment using high-pressure water flow, the average fiber diameter of the ultrafine fibers is preferably 1μm to 5μm.

[0021] From the viewpoint of easier entanglement treatment by high-pressure water jets, further improved wear resistance, and easier handling, the weight per unit area of ​​the ultrafine fiber nonwoven fabric is preferably 0.1 g / m 2 ~7g / m 2 , more preferably 0.3 g / m 2 ~5g / m 2 .

[0022] The first long fiber nonwoven fabric, the ultrafine fiber nonwoven fabric, and the second long fiber nonwoven fabric used in the present invention may contain various known additives such as antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, and fatty amides. The content of these additives in each nonwoven fabric is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, and even more preferably 0.01% by mass or less.

[0023] The first long fiber nonwoven fabric, the ultrafine fiber nonwoven fabric, and the second long fiber nonwoven fabric can be obtained by laminating them after being manufactured independently, but generally, it is preferably obtained by the following method. That is, an ultrafine fiber web obtained by the so-called melt-blown method is laminated on the first long fiber web obtained by the so-called spunbond method, and a second long fiber web obtained by the so-called spunbond method is further laminated on the ultrafine fiber web. Thereafter, the fibers in each web are locally fused to each other by hot embossing to obtain an SMS nonwoven fabric in which the first long fiber nonwoven fabric, the ultrafine fiber nonwoven fabric, and the second long fiber nonwoven fabric are laminated in this order.

[0024] A laminate is obtained by laminating a cotton fiber web, a first long fiber nonwoven fabric, an ultrafine fiber nonwoven fabric, and a second long fiber nonwoven fabric in sequence. At this time, it is preferred to laminate an SMS nonwoven fabric on the cotton fiber web to obtain a laminate. This is because it is easier to treat the laminate in the form of a high-strength SMS nonwoven fabric than to treat the ultrafine fiber nonwoven fabric alone. Then, a high-pressure water flow is applied to the laminate. The high-pressure water flow can be applied from the cotton fiber web side, from the second long fiber nonwoven fabric side, or from both sides. Through the action of the high-pressure water flow, the cotton fibers and the long fibers are interwoven, but the ultrafine fiber nonwoven fabric is destroyed, and the ultrafine fibers are cut off or flow out with the high-pressure water flow. However, a portion of the ultrafine fibers are retained and entangled in the interwoven portions between the cotton fibers or the interwoven portions between the long fibers. That is, the cotton fibers are entangled in the interwoven portions between the cotton fibers, making the bonding between the cotton fibers stronger. With this action, the wear resistance of the cotton fiber web side, that is, the surface material in contact with the skin, is improved. Furthermore, by destroying the ultrafine fiber nonwoven fabric, the nonwoven fabric no longer has a waterproof function, and becomes a surface material having body fluid permeability that allows body fluid to pass appropriately.

[0025] On the side of the second long fiber nonwoven fabric, any other fiber web can be laminated. For example, a mixed fiber web composed of cotton fiber and hot-melt short fiber can be laminated. The unit weight of the mixed fiber web is 10 to 20 g / m 2The mixing ratio of cotton fiber and hot-melt staple fiber in the mixed fiber web is preferably cotton fiber: hot-melt staple fiber = 100: 50-150 (mass ratio). As cotton fiber, it is preferred to use the above-mentioned undegreased cotton and undegreased bleached cotton. As hot-melt staple fibers, substances formed of thermoplastic resins having a melting point can be used. For example, polypropylene fiber, polyester fiber or polyamide fiber can be used. In the present invention, it is preferred to use hot-melt staple fibers that are concentric core-sheath type composite staple fibers and have a sheath component with a lower melting point than the core component. By softening or melting only the sheath component of the core-sheath type composite staple fibers, the fibers are fused and bonded to each other. In order to prevent the composite staple fibers from shrinking when only the sheath component is softened or melted, it is preferred to pre-become a concentric core-sheath type. If the hot-melt staple fibers shrink, the surface material obtained is prone to wrinkles, etc. Specifically, concentric core-sheath type composite staple fibers with a core component of polypropylene and a sheath component of polyethylene, and concentric core-sheath type composite staple fibers with a core component of polyester and a sheath component of polyethylene can be used. The fineness and fiber length of the heat-fusible staple fibers are optional, but generally, the fineness is about 1 to 5 dtex and the fiber length is about 10 to 100 mm.

[0026] Since the laminate contains water due to the high-pressure water flow, it is dried to evaporate the water. Thus, a surface material of a sanitary material can be obtained. When the laminate contains hot-melt staple fibers, it is preferred that the hot-melt staple fibers are softened or melted during or after the drying process, so that the fibers are fused and bonded to each other. For example, when a concentric core-sheath composite staple fiber in which the core component is polypropylene and the sheath component is polyethylene is used as the hot-melt staple fiber, if the drying temperature is about 130°C, the polyethylene softens or melts while the water evaporates, and the fibers are fused and bonded to each other, so that a surface material with excellent morphological stability can be obtained.

[0027] The obtained surface material is a surface material of a sanitary material including a cotton fiber web region composed of cotton fibers and a region containing long fibers containing propylene polymers, and ultrafine fibers having a fiber diameter thinner than the fiber diameter of the cotton fibers and the long fibers interlaced with the cotton fibers and the long fibers. Here, the cotton fiber web region and the region containing the long fibers are not clearly distinguished, and the fibers of each region can invade other regions. That is, the region with relatively more cotton fibers becomes the cotton fiber web region, and the region containing relatively more long fibers becomes the region containing the long fibers. The amount of each fiber in each region can be obtained by cutting the surface material of the sanitary material in the thickness direction, observing its cross section with a microscope, and counting the number of each fiber.

[0028] The thickness of the surface material is preferably 0.50 mm or less. If the thickness is 0.50 mm or less, the interweaving of the cotton fiber and the ultrafine fiber in contact with the skin is further improved, and there is a tendency for the wear resistance to be further improved. The surface material of the sanitary material of such thickness can be manufactured, for example, by the manufacturing method of the present invention. From the viewpoint of further improving the strength, the thickness is preferably 0.25 mm or more. The unit weight of the surface material of the sanitary material is preferably 25 g / m 2 ~50g / m 2 If the unit area weight is 25g / m 2 On the other hand, if the weight per unit area is 50 g / m 2 Thereafter, the interweaving of cotton fibers and ultrafine fibers in the cotton fiber web region increases, and a tendency is generated to improve the abrasion resistance.

[0029] For the tensile strength of the surface material of the sanitary material, the tensile strength in the mechanical direction is preferably 15N / 50mm wide to 100N / 50mm wide, more preferably 25N / 50mm wide to 90N / 50mm wide, and further preferably 30N / 50mm wide to 85N / 50mm wide. In addition, the tensile strength in the direction (width direction) orthogonal to the mechanical direction is preferably 10N / 50mm wide to 50N / 50mm wide. If the tensile strength is lower than the lower limit, a tendency of decreased handleability during the manufacture of sanitary materials is generated. In addition, if the tensile strength exceeds the upper limit, it becomes a surface material of excessive quality, which is unreasonable. Here, the mechanical direction refers to the conveying direction when manufacturing nonwoven fabrics. That is, the direction in which the long fibers in the nonwoven fabric are arranged. Therefore, the tensile strength in the mechanical direction as the arrangement direction of the long fibers is high, and the tensile strength in the width direction is low.

[0030] The surface material obtained as above can be used as the surface material of sanitary materials such as physiological sanitary napkins, disposable diapers and masks. And, because it is used in a way that the cotton fiber web side contacts the skin, the skin feel is good.

[0031] Example

[0032] Hereinafter, the present invention will be described based on examples, but the present invention is not limited to the examples. It should be noted that the following physical properties and characteristics used in this specification were measured by the following measurement methods.

[0033] (1) Weight per unit area (g / m 2 )

[0034] Take 10 samples of 100 mm in the machine direction and 100 mm in the width direction from the surface material or nonwoven fabric. Then, measure the mass of each sample and divide the total mass by the total area to calculate the unit area weight (g / m 2).

[0035] (2) Thickness (mm)

[0036] A thickness gauge (manufactured by PEACOCK, model "R1-250", measuring terminal 25 mm φ) was used with a load of 7 g / m 2 The thickness was measured at five points, namely the center and four corners, of the sample for which the basis weight was measured. The thickness was measured at 10 points of the sample for which the basis weight was measured by this method, and the average value was taken as the thickness (mm).

[0037] (3) Tensile strength in machine direction (N / 50mm width)

[0038] A sample with a size of 200 mm in the machine direction and 50 mm in the width direction was taken from the surface material. Then, based on JIS L1913, a tensile tester (manufactured by Shimadzu Corporation, Autograph AGS-J) was used to measure the breaking strength of each sample under the conditions of a chuck distance of 100 mm and a chuck of 300 mm / min. The average value of the breaking strength of the 5-point sample was taken as the tensile strength in the machine direction (N / 50 mm width).

[0039] (4) Tensile strength in width direction (N / 50mm width)

[0040] Take samples of 50 mm in the machine direction and 200 mm in the width direction from 5 points on the surface material. Then, measure the breaking strength of each sample by the same method as above (3). The average value of the breaking strength of the 5-point samples is taken as the tensile strength in the width direction (N / 50 mm width).

[0041] (5) Wear resistance (times)

[0042] Take 50 samples of 293mm in length and 165mm in width from the surface material in random directions. Six of the samples are set in a Gakushin type friction fastness tester (manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd., model "RT-300") based on JIS L 0849, with the cotton fiber mesh surface becoming the friction terminal side, and the wear resistance is measured. When setting the sample, a urethane pad is pre-laid under the sample, and it is fixed to a fixture equipped with a Gakushin type friction fastness tester in a wrinkle-free manner. In addition, cover the surface of the friction terminal with a cloth adhesive tape, apply a load of 300g to the friction terminal, and make the cloth adhesive tape contact the sample. Then, slide the friction terminal at a reciprocating speed of 30 times / minute, and measure the number of reciprocating times when all 6 samples can be observed to be broken. Carry out this measurement 5 times, and take their average value as the wear resistance (times). Even if the number of reciprocating times exceeds 500, the measurement is stopped when no cracks are observed in any of the six-point samples, and the number of reciprocating times is set to 500. Therefore, 500 times is the maximum value of the wear resistance (times).

[0043] (6) Average fiber diameter of long fibers

[0044] The measurement is performed based on an electron microscope photograph of the surface of a long fiber nonwoven fabric. Specifically, a method for measuring the average fiber diameter of long fibers using an SMS nonwoven fabric is described. A photograph of the surface of the SMS nonwoven fabric at a magnification of 300 times is taken using an electron microscope (manufactured by Hitachi, Ltd., model: S-3500N). In the photograph taken, the photographs are taken repeatedly until the number of fibers with a fiber diameter of 9 μm or more closer to the surface side than the ultrafine fibers reaches a total of 50 (n=50) or more. In the obtained photograph, the diameter (width) of all fibers with a fiber diameter of 9 μm or more located on the surface side of the ultrafine fibers is measured, and the arithmetic mean thereof is taken as the average fiber diameter of the long fibers in the long fiber nonwoven fabric on the surface side. The back side is also measured in the same way.

[0045] (7) Average fiber diameter of ultrafine fibers

[0046] The measurement is performed based on an electron microscope photograph of the surface of an ultrafine fiber nonwoven fabric. Specifically, a method for measuring the average fiber diameter of ultrafine fibers using SMS nonwoven fabric is described. A photograph of the surface of the SMS nonwoven fabric at a magnification of 2000 times is taken using an electron microscope (manufactured by Hitachi, Ltd., model: S-3500N). In the photograph taken, the photographs are taken repeatedly until the total number of fibers with a fiber diameter of less than 8 μm reaches 50 (n=50) or more. In the obtained photograph, the diameter (width) of all fibers with a fiber diameter of less than 8 μm is measured, and the arithmetic mean thereof is taken as the average fiber diameter of the ultrafine fibers in the ultrafine fiber nonwoven fabric.

[0047] It should be noted that in (6) and (7) above, the diameter (width) of the fiber can be measured at the position where the fiber width is the smallest in the photograph. In addition, when the fibers are fused to each other, it is sufficient to measure the unfused portion. If there is no unfused portion, it can be excluded from the number of fibers.

[0048] Example 1

[0049] [Preparation of cotton fiber web]

[0050] The undegreased bleached cotton with an average fiber length of 25 mm was opened and gathered using a parallel carding machine to obtain a unit area weight of 20 g / m 2 Cotton fiber mesh.

[0051] [Preparation of SMS nonwoven fabric]

[0052] A propylene homopolymer with a melting point of 162°C and MFR of 60g / 10min (MFR is measured based on ASTM D1238 at a temperature of 230°C and a load of 2.16kg. The method for measuring MFR is the same below) is used. A spinning head with a plurality of spinning holes of 0.6mmφ is used at a melting temperature of 230°C. Melt spinning is performed by a conventional spunbond method, and the long fibers are gathered on the collection surface to obtain a first long fiber web. The average fiber diameter of the long fibers in the first long fiber web is 12.8μm, and the unit area weight of the first long fiber web is 5.75g / m 2 .

[0053] Next, a propylene homopolymer having a melting point of 160°C and an MFR of 400 g / 10 minutes was used, and a molten melt was discharged from a die having a plurality of discharge holes of 0.4 mmφ at a melting temperature of 280°C, and ultrafine fibers were gathered on the first long fiber web by a conventional melt-blowing method in which heated air at 280°C was blown at the outlet of the discharge holes, thereby obtaining an ultrafine fiber web. The average fiber diameter of the ultrafine fibers in the ultrafine fiber web was 1.4 μm, and the unit area weight of the ultrafine fiber web was 1.5 g / m 2 .

[0054] The same method as the method for obtaining the first long fiber web was carried out, and the long fibers were gathered on the ultrafine fiber web to obtain a second long fiber web. The average fiber diameter of the long fibers in the second long fiber web was 12.8 μm, and the unit area weight of the second long fiber web was 5.75 g / m 2 .

[0055] The web in which the first long fiber web, the ultrafine fiber web and the second long fiber web are sequentially laminated is locally heat-pressed by a heat embossing roll at a temperature of 145°C and a mirror roll at a temperature of 150°C so that the total press-bonding area becomes 18%, and the three layers are integrated to obtain an SMS nonwoven fabric in which the first long fiber nonwoven fabric, the ultrafine fiber nonwoven fabric and the second long fiber nonwoven fabric are sequentially laminated. It should be noted that the unit area weight of the SMS nonwoven fabric is 13 g / m 2 .

[0056] The laminated body of the cotton fiber web and SMS nonwoven fabric prepared above was passed through a high-pressure water jet device (a device in which the jet holes with a hole diameter of 0.1 mm are arranged in a horizontal row with a hole interval of 0.6 mm), and a high-pressure water jet was applied from the cotton fiber web side at a jet pressure of 3 MPa, and then a high-pressure water jet was applied at a jet pressure of 6 MPa. Thereafter, a high-pressure water jet was applied from the second long fiber nonwoven fabric side at a jet pressure of 6 MPa, and then dried at 120° C. to obtain a surface material.

[0057] Example 2

[0058] [Preparation of cotton fiber web and SMS nonwoven fabric]

[0059] The same cotton fiber web and SMS nonwoven fabric as those used in Example 1 were obtained.

[0060] [Preparation of mixed fiber web]

[0061] As the hot-melt staple fibers, concentric core-sheath composite staple fibers (manufactured by Unitika Co., Ltd., fineness 2.2 dtex, fiber length 51 mm) were used, in which the sheath component was polyethylene with a melting point of 130°C and the core component was polyethylene terephthalate with a melting point of 260°C. Then, 50% by weight of undegreased bleached cotton with an average fiber length of 25 mm and 50% by weight of the hot-melt staple fibers were uniformly mixed, opened and gathered using a random carding machine, and a weight per unit area of ​​17 g / m 2 Mixed fiber mesh.

[0062] The laminated body of the cotton fiber web, SMS nonwoven fabric and mixed fiber web prepared above was sequentially laminated through the high-pressure water jet device used in Example 1, and the high-pressure water jet was applied from the cotton fiber web side at a jet pressure of 3 MPa, and then at a jet pressure of 6 MPa. Thereafter, the high-pressure water jet was applied from the mixed fiber web side at a jet pressure of 6 MPa, and then dried to obtain a surface material. It should be noted that when the drying temperature is 135°C, only the polyethylene of the concentric core-sheath type composite short fibers softens or melts, thereby obtaining a surface material in which the fibers are fused and bonded to each other.

[0063] Example 3

[0064] In the SMS nonwoven fabric used in Example 1, the weight per unit area of ​​the first long fiber web and the second long fiber web was changed to 6.25 g / m 2 , and the unit area weight of the ultrafine fiber web was changed to 0.5g / m 2 , except for this, a surface material was obtained in the same manner as in Example 1. It should be noted that the change in the basis weight was performed by adjusting the moving speed of the collection surface and the discharge amount of the ultrafine fibers.

[0065] Comparative Example 1

[0066] No SMS nonwoven fabric is used, only 35g / m2 per unit area weight is used 2 A cotton fiber web was subjected to high pressure water flow under the same conditions as in Example 1 to obtain a weight per unit area of ​​35 g / m 2 surface material.

[0067] Comparative Example 2

[0068] A filament web having a weight of 33 g / m2 was obtained in the same manner as in Example 1 except that a long fiber web obtained by the following method was used instead of the SMS nonwoven fabric. 2 surface material.

[0069] [Manufacturing of long fiber web]

[0070] A propylene homopolymer with a melting point of 162°C and an MFR of 60 g / 10 min was used, and melt spinning was performed at a melting temperature of 230°C using a spinning head with multiple spinning holes of 0.6 mm φ, and the long fibers were gathered on the collecting surface to obtain a long fiber web. The average fiber diameter of the long fibers in the long fiber web was 33.5 μm, and the unit area weight of the long fiber web was 13.0 g / m 2 .

[0071] The surface materials obtained in Examples 1 to 3, Comparative Examples 1 and 2 were evaluated for their weight per unit area, thickness, tensile strength in the machine direction, tensile strength in the width direction, and abrasion resistance by the above-mentioned method. The results are shown in Table 1. According to the results in Table 1, it can be seen that the surface materials obtained in the Examples have excellent abrasion resistance on the surface in contact with the skin.

[0072] [Table 1]

[0073]

Claims

1. A method for producing a surface material of a sanitary material whose cotton fiber web side contacts the skin, characterized in that: A high-pressure water flow is applied to a laminated body formed by laminating a cotton fiber web and an SMS nonwoven fabric composed of cotton fibers, thereby destroying the ultrafine fiber nonwoven fabric and cutting the ultrafine fibers, and causing the cotton fibers to be entangled with the ultrafine fibers. Then, a drying process is performed to evaporate the water from the high-pressure water flow. The SMS nonwoven fabric is formed by sequentially laminating a first long fiber nonwoven fabric composed of long fibers containing a propylene-based polymer and obtained by a spunbond method, an ultrafine fiber nonwoven fabric composed of ultrafine fibers and obtained by a meltblowing method, and a second long fiber nonwoven fabric composed of long fibers containing a propylene-based polymer and obtained by a spunbond method, and the first long fiber nonwoven fabric, the ultrafine fiber nonwoven fabric and the second long fiber nonwoven fabric are locally heat-pressed and fused by heat embossing. The ultrafine fibers contain a propylene polymer and have a fiber diameter that is thinner than that of the cotton fibers and the long fibers.

2. The method for producing a surface material of a sanitary material according to claim 1, wherein: The cotton fiber is undegreased and bleached cotton fiber.

3. The method for producing a surface material of a sanitary material according to claim 1 or 2, wherein: The unit weight of ultra-fine fiber non-woven fabric is 0.1g / m 2 ~7g / m 2 .

4. The method for producing a surface material of a sanitary material according to claim 1, wherein: As a laminate, a laminate is used in which a mixed fiber web composed of cotton fibers and heat-fusible short fibers is laminated on the second long fiber nonwoven fabric side in the SMS nonwoven fabric. During the drying process, the heat-fusible short fibers are softened or melted, so that the cotton fibers, ultrafine fibers and long fibers are fused and bonded to each other.

Citation Information

Patent Citations

  • Absorbing article

    JP1997117470A

  • Absorbent article

    JP2019209121A

  • Method of preparing polypropylene multi-layer nonwoven fabrics for medical treatment

    CN101358410A

  • Topsheet for absorbent articles

    JP3218416U